Photographic evidence of Himalayan Serow Capricornis sumatraensis ssp. thar (Hodgson, 1831) in Bardia National Park, Nepal - Yadav, Shailendra; Lamichhane, Babu; Thapa, Shyam; Kadariya, Rabin; Paudel, Umesh; Subedi, Naresh (Bulletin of Basrah Natural History Museum, 2022)
Himalayan Serow (Capricornis sumatraensis ssp. thar Hodgson, 1831) believed to be distributed only in Bangladesh, Bhutan, China, India and in Nepal. It occurs across the Churia - Himalayan range and has also been detected within the Annapurna Conservation Area, Langtang and Makalu Barun National Park. Recently it was discovered from wider areas than previously thought but never recorded from Bardia National Park (BNP). During a camera trap survey primarily targeted for tigers Panthera tigris, Himalayan Serow was photographed multiple times on four camera trap stations in BNP in December 2017 and January 2018. The camera trapped location is in dry-deciduous mixed forest mainly composed of hill Sal Shoresa robusta, Saj Terminalia tomentosa forest in core area of the park at a distance of approximately 15 km from settlements. This is the first photographic evidence of Himalayan Serow captured in BNP, Nepal. Similarly, a single record exists, from a rescue in 2013, of a Himalayan Serow at Kalinara in the Babai Valley (along the Babai River) of the Park. As stated by the BNP and Buffer Zone Management Plan (2016 – 2020), a total of 56 mammal species are reported from the park and with this record adds one more mammal species in the park. The study revealed that camera trapping targeted at tigers can provide opportunity for getting important information on rare and elusive species. Himalayan Serow co-exist in Bardia with sympatric herbivores like Four Horned Antelope Tetra cerusquadri cornis, Himalayan Crestless Porcupine Hystrix brachyuran, and Sambar Rusa unicolor and other animal like Tiger Panthera tigris and Sloth bear Melursus ursinus.